Implementasi Teknologi Internet Sebagai Solusi Pengentasan Masalah Komunikasi di Desa Nyamuk, Kecamatan Karimunjawa, Kabupaten Jepara - Bakhtiar Alldino Ardi Sumbodo; Andi Dharmawan; Faizah Faizah (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
Nyamuk Village is a village in the form of an island in Karimunjawa Islands, which is located at 5°48'33.44" S - 5°49'11.78" S and 110°10'51.09" E - 110°11'53.85" E. The majority of people working as a fisherman and a small proportion become craftsmen, farmers, traders, and government officials. The village has marine resources are very abundant, but the distance which reaches 28.6 km from the District of Karimunjawa, make this village a more isolated than the other islands in Karimunjawa Islands. Limited access to communication, information, and education in this community become one of the issues that need to be resolved. GSM phone signal range that does not exist and the lack of internet access, making communication, information, and education in this village are still underdeveloped. The solution to overcoming these problems, it is necessary to implement Internet technology to improve access to communications, information, and education in the Nyamuk Village, Karimunjawa Islands. The existence of free internet access in this village is expected to have a positive impact and improve the lives of the community.